Case report: A case of neoadjuvant immunotherapy in combination with the Yang–Monti technique for the treatment of ureteral carcinoma after radical cystectomy and left radical nephroureterectomy - Wu, Tielin; Haleem, Harris; Yin, Min (Frontiers in Oncology, 2022)
Abstract Background: Recurrence of urothelial carcinoma in a patient with solitary kidney is always a clinical challenge. In immune checkpoint inhibitors era, neoadjuvant immunotherapy in combination with Yang–Monti technique might be a good option for the patient with a high-risk tumour when kidney-sparing surgery for renal function preservation is desired. Case description: A 74-year-old man with solitary kidney was diagnosed with recurrence of urothelial carcinoma in the right ureteral. He was initially deemed unfit for segmental resection of the ureter. Neoadjuvant immunotherapy with Tislelizumab was performed to this patient with a partial response of the urothelial carcinoma. He underwent segmental resection of the ureter with negative margins and the ureteral defect was bridged by modified ileal replacement, which is the Yang-Monti technique. This patient has remained disease-free with adequate kidney function for longer than 18 months. Conclusion: Tislelizumab in combination with Yang–Monti technique was an available option in the treatment of ureteral carcinoma accompanied by solitary kidney.